An exploration of Difficulties and Strategies Encountered by Yemeni EFL Undergraduates in understanding idiomatic expressions - Al-Aliee, Faten (International Journal of Language and Literary Studies, 2025)
Idiomatic expressions are an integral part of English proficiency, reflecting both linguistic and cultural competence. However, they present persistent challenges for non?native speakers due to their figurative nature, cultural specificity, and lack of direct equivalents in learners’ first language. This study investigated the difficulties Yemeni undergraduate EFL learners face in understanding idiomatic expressions and explored the strategies they employ to overcome these challenges. A structured questionnaire was administered to 30 level?four English major students at Sana’a University. Data were analyzed using descriptive statistics (means, standard deviations, frequencies) and inferential analysis via SPSS to identify patterns and potential differences across gender and educational background. The findings revealed that learners’ main obstacles stemmed from limited cultural knowledge, insufficient exposure to idioms in authentic contexts, and the arbitrariness of idiomatic meanings. To address these challenges, students reported using strategies such as guessing meaning from context, literal interpretation, consulting L1 equivalents, memorization, and visualization. No significant differences were observed based on gender, suggesting that, within this small group of Yemeni EFL undergraduates at Sana’a University, the reported difficulties and strategies were broadly shared. Given the limited sample size and single?institution context, these findings should be viewed as preliminary and cannot be generalized to all advanced EFL learners. The study highlights the pedagogical importance of systematic instruction in idioms, emphasizing contextualized practice, authentic materials, and interactive classroom activities. Incorporating these approaches can enhance learners’ comprehension and production of idiomatic expressions and contribute to both linguistic proficiency and cultural competence. These findings offer practical insights for EFL educators seeking to improve idiomatic competence, which remains a key marker of advanced English mastery.